Labor human rights and human dignity. (February 2016) - Gilabert, Pablo
The current legal and political practice of human rights invokes entitlements to freely chosen work, to decent working conditions, and to form and join labor unions. Despite the importance of these rights, they remain under-explored in the philosophical literature on human rights. This article offers a systematic and constructive discussion of them. First, it surveys the content and current relevance of the labor rights stated in the most important documents of the human rights practice. Second, it gives a moral defense of these rights arguing that their support involves an appropriate response to important human interests and to the human dignity of workers. Finally, it explores central normative issues about the relation between labor rights and human dignity. It responds to some objections about the importance of work, explains why labor human rights may not exhaust the demands of dignity regarding labor and arbitrates a common tension between independence and solidarity within our practical affirmation of human dignity.